Lying and Truthfulness: A Thomistic Perspective by Stewart Clem, Cambridge University Press, Cambridge, 2023, pp. xiv+213, £85, hbk - Crsa, Margaret Atkins (New blackfriars, 2024)
Lying and Truthfulness: A Thomistic Perspective by Stewart Clem, Cambridge University Press, Cambridge, 2023, pp. xiv+213, £85, hbk - Volume 105 Issue 6